EFISIENSI BIAYA PROYEK MELALUI PERUBAHAN DISAIN PADA PEKERJAAN FINISHING KAYU - Ni Kadek Sri Ebtha Yuni (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2021)
Project cost efficiency can be done in things such as value engineering. The value engineering process can be carried out at the conceptual, planning and implementation stages of the project. Design changes also have an impact that affects the performance of construction implementation. Currently wood material is still widely used for finishing work, such as the roof of a pergola, room dividing walls, or just as a glass clamp. This research uses quantitative descriptive analysis, which begins by calculating the volume of work, determining the coefficient of wood material, compiling a unit price analysis, calculating the budget for existing designs and changing designs, making comparisons between the two designs. The unit price of the existing design for a room dividing work with 30x50 mm wood including a frame with 50x70 mm wood is IDR 2,597,451 per m2. For roof work, timber lattice pergola with 40x60 mm wood is Rp. 848,726 per m2, and grilling work for lattice with 40x60 mm wood is Rp. 777,070 per m2. The total budget for the existing design is Rp. 335,303,754.84. The total cost budget with the design change is IDR 289,335,447.58. The cost efficiency between the existing design and design changes is IDR 45,968,307 or 15.90%